2017
DOI: 10.1007/s11678-017-0415-3
|View full text |Cite
|
Sign up to set email alerts
|

Chondral defects of the glenohumeral joint

Abstract: IntroductionAn increasing number of young patients are diagnosed with chondral lesions. Minimally invasive surgical techniques are important in order to delay progression of the early stages of osteoarthritis and the need for total joint replacement.Materials and methodsPatients (n = 32) who had received microfracturing of the shoulder were retrospectively enrolled, of whom 5 had received shoulder replacements after a mean time of 47 months. Of these patients, 23 completed the Disabilities of the Arm, Shoulder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 17 publications
(19 reference statements)
4
23
0
Order By: Relevance
“…However, both of the patients requiring revision surgery had isolated (1 humeral and 1 glenoidal) and not bipolar lesions. Another recent study by Hünnebeck et al 25 is widely in accordance with our data, describing very satisfying clinical long-term outcome following glenohumeral microfracturing. However, they also reported less favorable outcome when lesions were bipolar.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, both of the patients requiring revision surgery had isolated (1 humeral and 1 glenoidal) and not bipolar lesions. Another recent study by Hünnebeck et al 25 is widely in accordance with our data, describing very satisfying clinical long-term outcome following glenohumeral microfracturing. However, they also reported less favorable outcome when lesions were bipolar.…”
Section: Discussionsupporting
confidence: 93%
“…Another recent study by Hünnebeck et al. 25 is widely in accordance with our data, describing very satisfying clinical long-term outcome following glenohumeral microfracturing. However, they also reported less favorable outcome when lesions were bipolar.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the methodology of our study was not designed to determine if operative treatment of chondral lesions was effective, as it was limited by selection bias (subjective decision making by the surgeon to perform cartilage treatment) and small sample size (17 chondroplasties, 9 microfractures). Regardless of this, multiple studies 2 , 3 , 7 , 8 , 19 , 22 24 have demonstrated the effectiveness of both chondroplasty and microfracture in the treatment of chondral damage. Similar to our study, Kerr and McCarty 10 demonstrated that when treating chondral injuries without rotator cuff tears, outcomes were similar regardless of whether the Outerbridge classification was grade 2-3 or grade 4.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the size of the lesion dictates treatment. Small, superficial osteochondral defects can be treated with micro-fracture and debridement 60. Cameron et al reported 88% of patients experiencing significant pain relief over an average of 28 months;61 Gross et al found good or excellent results in 78% of patients at 30 months 62…”
Section: Introductionmentioning
confidence: 99%